Earthquake slip vectors in the Himalayan thrust Zone and their tectonic implications (MAUSAM, 1993)
Slip vectors of thirty-nine thrust events occurring along the Himalayan collision zone have been compared with the velocity vectors between the Indian-Eurasian plates derived from the RM 2 and NUVEL 1 models, The observed deviations of the slip vector from the velocity vector have been interpreted in terms of a simple kinematic model according to which the eastern and western blocks of south Tibet are separating from each other, From the model it is estimated that the western and eastern blocks of Tibet are moving at the rate of 3.6 cm/year westwards at 76°Eand 2.6 cm/year eastwards at 94°E with respect to Eurasia respectively, resulting in an east-west extension, projected to the trend at 85°E, at the rate of 5, 5 cm/year. This would correspond to a strain rate of about 6.9 x 10-8year in central Tibetan region.